Osimertinib- Cardiac Dysfunction with Prolonged QTc Interval: A Case Report - Medepalli, Lalitha C.; Jolly, Pradeep C.; Vallakati, Ajay; Medepalli, Anita M. (Cardiology and Cardiovascular Medicine, 2022)
Background: Osimertinib has improved outcomes and is indicated by Food and Drug Administration (FDA) for epidermal growth factor receptor (EGFR)-mutated lung cancer. Osimertinib use is associated with cardiac-related adverse events, including cardiac dysfunction and prolonged QTc interval. There is an increasing need for a comprehensive evaluation prior to the initiation of Osimertinib with a detailed assessment of clinical history particularly looking at the cardiovascular risk factors, a protocol-driven close cardio-oncology with periodic electrolyte and ECG monitoring during the therapy, as these high-risk patients are associated with higher rates of cardiotoxicity compared with the low-risk patient population. Introduction: We report a patient who presented with cardiomyopathy, manifested by prolonged QTc interval, new valvular and left ventricular systolic dysfunction, six months into her treatment with Osimertinib. With timely detection and treatment of her electrolyte abnormality and poor oral intake, we were able to correct the markedly prolonged QTc interval and prevent potential life-threatening arrhythmia. Conclusions: Patients receiving third-generation tyrosine kinase inhibitor, Osimertinib, should be carefully monitored for the development of cancer treatment-related cardiac dysfunction (CTRCD). A significant number of these patients also have other associated cardiac risk factors and comorbidities including poor nutrition. With poor per oral (PO) intake due to comorbidities, this subgroup of patients is even more susceptible to significant electrolyte abnormalities. Our case highlights the importance of close monitoring of especially these patients with regular electrocardiograms (EKGs), and electrolyte panels, along with the assessment of left ventricular function when needed to detect and interven